TanggungJawab Polri dalam Pengamanan Calon Kepala dan Wakil Kepala Daerah di Kota Denpasar - Dimas Putra Wicaksana; Agung Anak Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
The responsibility of the National Police in securing the candidates who will be elected as regional heads and also their deputy is a responsible action during the regional head elections, therefore the police apparatus is very important in maintaining security and order during the election. This study examines the form of security for candidates for regional heads and deputy regional heads in Denpasar City and explains the responsibility of the National Police for the security of candidates for regional heads and deputy regional heads in Denpasar City. The research method used is an empirical legal research method, with a statutory approach. The data used are primary and secondary data obtained by interview, observation and documentation techniques. The results of the study indicate that the security procedures for candidates who will be elected as regional heads and also their representatives in Denpasar City are referred to the rules implemented by the Denpasar Police and based on Article 5 paragraph (2) of Law No. 2 of 2002 concerning the Police. While the responsibility of the National Police for the security of candidates who will be elected as regional heads and also their representatives in Denpasar City is as the bearer of obligations, especially under the command of the Chief of Police, one of the main tasks of carrying out these obligations is the role of the Police as an intelligence unit in overcoming potential security disturbances.